Low rates of myocardial fibrosis and ventricular arrhythmias in recreational athletes after SARS-CoV-2 infection - Miljoen, Hielko; Favere, Kasper; Van De Heyning, Caroline; Corteville, Ben; Dausin, Christophe; Herbots, Lieven; Teulingkx, Tom; Bekhuis, Youri; Lyssens, Malou; Bogaert, Jan; Heidbuchel, Hein; Claessen, Guido (Frontiers in Cardiovascular Medicine, 2024)
Following the identification of the SARS-CoV-2 virus, hHigh rates of cardiac involvement were initially reported in the beginning of the COVID-19 pandemic. This led to anxiety in the athletic population. The current study was set up to assess the prevalence of myocardial fibrosis and ventricular arrhythmias in recreational athletes with recent SARS-CoV-2 infection.Consecutive adult recreational athletes (≥18 years old, ≥4 hours of mixed type or endurance sports/week) over 18 years old, performing more than four hours of endurance or mixed type sports per week and not suffering from previous cardiac disease or claustrophobia underwent systematic cardiac evaluation after a prior confirmed COVID-19 infection. Evaluation included clinical history, ECG, five-day Holter monitoring and cardiac magnetic resonance imaging (CMR) with simultaneous measurement of cardiac high-sensitive cardiac Troponin IhsTrop-I. Data from asymptomatic or mildly symptomatic athletes (Group 1) were compared to those with moderate to severe symptoms (Group 2-3). Furthermore, a comparison with a historical control group of athletes without COVID-19 (Master@Heart) was made.In total, 35 athletes (18 Group 1, 10 female, 36.9±2.2 years, mean 143±20 days post-diagnosis) were evaluated. Baseline characteristics for Group 1 and Group 2-3 athletes were similar. None of the athletes showed overt myocarditis on CMR based on the updated Lake Louise criteria for diagnosis of myocarditis. Prevalence of There was no difference in the occurrence of nonnon-ischemic late gadolinium enhancement (1 (6%) Group 1 vs. 2 (12%) GGroup 2-3; p=0.603) or ventricular arrhythmias (1 Group 1 athlete showed nonsustained ventricular tachycardia (vs. 0 in Group 2-3: p=1.000)) were not statistically different between the groups. When the male athletes were compared to Master@Heart athletes, there were alsoagain no differences regarding these criteria were found.In our series of recreational athletes with prior confirmed COVID-19, we found no evidence of ongoing myocarditis, and no more detection of fibrosis or ventricular arrhythmias than in a comparable athletic pre-COVID cohort. This , pointings to a much lower cardiac involvement of COVID-19 in athletes than originally suggested.